Phenotypic and molecular detection of the blaKPC gene in clinical isolates from inpatients at hospitals in São Luis, MA, Brazil. Issue 1 (December 2016) - Ribeiro, Patricia; Monteiro, Andrea; Marques, Sirlei; Monteiro, Sílvio; Monteiro-Neto, Valério; Coqueiro, Martina; Marques, Ana; de Jesus Gomes Turri, Rosimary; Santos, Simone; Bomfim, Maria
Abstract Background Bacteria that produceKlebsiella pneumoniae carbapenemases (KPCs) are resistant to broad-spectrum β-lactam antibiotics. The objective of this study was to phenotypically and genotypically characterize the antibiotic susceptibility to carbapenems of 297 isolates recovered from clinical samples obtained from inpatients at 16 hospitals in São Luis (Maranhão, Brazil). Methods The study was conducted using phenotypic tests and molecular methods, including polymerase chain reaction (PCR), sequencing and enterobacterial repetitive intergenic consensus (ERIC)-PCR. The nonparametric chi-square test of independence was used to evaluate the associations between the bacterialbla KPC gene and the modified Hodge test, and the chi-square adherence test was used to assess the frequency of carbapenemases and their association with thebla KPC gene. Results The most frequently isolated species wereAcinetobacter baumannii (n = 128; 43.0%), K. pneumoniae (n = 75; 25.2%), andPseudomonas aeruginosa (n = 42; 14.1%). Susceptibility assays showed that polymixin B was active against 89.3% of the bacterial isolates. TheAcinetobacter spp. andK. pneumoniae strains were susceptible to amikacin and tigecycline, andPseudomonas spp. were sensitive to gentamicin and amikacin. Among the 297 isolates, 100 (33.7%) were positive for thebla KPC gene, including non-fermentative bacteria (A. baumannii ) andEnterobacteriaceae species. Among the isolates positive for thebla KPC gene, K. pneumoniae isolates had the highest positivity rate of 60.0%. Thebla KPC gene variants detected included KPC-2, which was found in all isolates belonging to species of theEnterobacteriaceae family. KPC-2 and KPC-3 were observed inA. baumannii isolates. Importantly, thebla KPC gene was also detected in threeRaoultella isolates and one isolate of thePantoea genus. ERIC-PCR patterns showed a high level of genetic diversity among the bacterial isolates; it was capable of distinguishing 34 clones among 100 strains that were positive forbla KPC and were circulating in 11 of the surveyed hospitals. Conclusions The high frequency of thebla KPC gene and the high degree of clonal diversity among microorganisms isolated from patients from different hospitals in São Luis suggest the need to improve the quality of health care to reduce the incidence of infections and the emergence of carbapenem resistance in these bacteria as well as other Gram-negative pathogens.